PENGEMBANGAN MEDIA PERMAINAN PUZZLE BERBASIS ANDROID UNTUK MATERI PECAHAN KELAS III SD - Fauziah, Jihan Nur; Sarifah, Iva; Adnan, Evita (Educational Technology Journal, 2024)
This research and development aims to produce a product and determine the feasibility of an Android-based puzzle game media for fractional material for grade III elementary school. This research was conducted in the researcher's home environment, namely, RW 001, Jakamulya Village, South Bekasi District, Bekasi City. The research method used is the research and development (R&D) method with the ADDIE development model (Analysis, Design, Development, Implementation and Evaluation). Data collection techniques using observation, interviews, and questionnaire. The data were analyzed using the Miles and Huberman analysis model. Respondents in this development are one material expert lecturer, one media expert lecturer, one language expert lecturer and third grade students in RW 001, Jakamulya Village, South Bekasi District, Bekasi City. The test results for developing Android-based puzzle game media to three experts (expert review) obtained an average value of 88% or the media was in the very good category. In addition, the results of the One to One trial stage are 95% and the Small Group is 98%. Referring to the results of data analysis of the Miles and Huberman model, the puzzle game media based on Android is a valid product and is suitable for use in learning mathematics in grade III Elementary School.